THE CATEGORY OF MODALITY: OBJECTIVE AND SUBJECTIVE MODALITY - Radjapova Nafisa Muminjonovna (Western European Studies, 2024)
The main research object of the article is the category of modality, the history of the origin of the semantic category, the information about the linguistic means representing it are included in this article. In addition, representatives of the school of Romance linguistics, moreover, English, German and Uzbek linguists have presented various opinions about this category and detailed comments about the linguistic units that represent it. At the end of the discussion part of the article, there is presented some information about objective and subjective modality, and the explained rules are proved with the help of various examples
Keywords: Modality; semantic category; objective and subjective modality